Composition and biotransformational changes in soluble microbial products (SMPs) along an anaerobic baffled reactor (ABR). (September 2020) - Soh, Yan Ni Annie; Kunacheva, Chinagarn; Webster, Richard D.; Stuckey, David C.
Abstract: This work examined the production and catabolism/biotransformation dynamics of SMPs down the length of an eight-compartment-anaerobic baffled reactor (ABR) which physically separates the biological processes, in contrast to completely mixed reactors which do not enable these dynamics to measured, and this is totally novel. SMPs were extracted and characterised by gas and liquid chromatography coupled mass spectrometry to determine their composition and production/catabolism. 60%–70% of the feed compounds decreased from the first to fourth compartment; the increase in SMPs after the fourth compartment suggested a mixture of degraded and biotransformed compounds, and microbial products. High concentrations of low MW alkanes and alkenes, and higher MW (up to 2000 Da) lipids and amino acid derivatives accumulate in the last compartment at pseudo-steady state, and past work identifying polysaccharides/peptides as major membrane biofoulants have excluded these lipids. In addition, lipids and changes detected during feed transients have not been noted before in previous work. Finally, feed step-increases also increased some amino acid derivatives used in cell-signalling. Interestingly, some natural products from plant and fungal extracts were also found in the fourth compartment, where methanogenesis was the dominant process. Highlights: Production and catabolism of SMPs down 8-compartment ABR in contrast to CSTR. Feed step-increases increase some amino acid derivatives used in cell-signalling. Lipids and changes detected during transients not noted before in previous work. Past work identifying polysaccharides/peptides as major biofoulants exclude lipids. Lipids present might cause fouling since always present in the final compartment.